PERAN EKSPRESI E-CADHERIN PADA METASTASIS KARSINOMA NASOFARINGS - , Taufiqurrahman ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Nasopharyngeal Carcinoma (NPC) tumor cells frequently invade surrounding tissue or metastasis at early stages of tumor development. The exact mechanisms of metastasis remain unknown. Many factors may be involved, such as cell adhesion molecules. E-cadherin plays an important role in maintenance of cell adhesions on epithelial cells. The loss of E-cadherin mediated cell adhesion is found to be an important step in promoting malignant metastatic potential in NPC. Epsteine Barr Virus (EBV) is associated with 90% of nasopharyngeal carcinoma (NPC), Latent membrane protein 1 (LMP1) is an oncogene of EBV which takes part in the regulation of tumor metastasis related genes such as E-cadherin. Objective: This study is aimed to determine the difference of E-Cadherin expression between the NPC patient that has metastasized and the NPC patient that has not metastasized. Methods: Research design was case control study. Subjects of this research were paraffin blocks of NPC patient who had undergone biopsy at the Otorhinolaryngology Head and Neck Surgery (ORL-HNS) department dr. Sardjito General Hospital of Yogyakarta. Paraffin blocks from NPC patients who had metastasized were categorized as cases group, while the non metastasized as a control group. Samples from both groups were examined with immunohistochemistry (IHC) method using E-cadherin antibody at the anatomical pathology Laboratory dr. Sardjito General Hospital of Yogyakarta. Statistical analysis to prove the hypothesis were using chi square. Result: Study sample were 48 paraffin blocks of NPC patients , each group consisted of 24 paraffin blocks. There was statistically significant difference E-caherin expression between the NPC patient that had metastasized and the NPC patient that had not metastasized with p<0.001 and Odds Ratio (RO): 87.4 (95% confidence interval 10.15 to 2653.26). Conclusion: There is significant difference of E-cadherin expression between the NPC patient that has metastasized and the NPC patient that has not metastasized. Keywords: Nasopharyngeal carcinoma, E-cadherin expression, metastasis